THE ROLE OF MICRORNA-200C IN CHEMORESISTANT ﻿BREAST CANCER - Agung Bagus Sista Satyarsa; IGP Supadmanaba; PAT Adiputra (Indonesian Journal for Health Sciences, 2020)
Breast cancer is a non-communicable diseases and also major health problem in the world. Based on data from WHO in 2012, the incidence of breast cancer reported as 1.67 million cases. One cause of highest morbidity and mortality in breast cancer is chemoresistancy. Many pathways could cause chemoresistant in breast cancer. The one of pathways are from genetic such as miR-200c. Base on the other study, mir-200c act an apoptosis inducer and inhibit metastasis in chemoresistant breast cancer cells. The mir-200c act the role in specific target cells in chemoresistant breast cancer. Meanwhile, the expression of miR-200c induces Mesenchymal Epithelial Transition (MET) by inhibits ZEB 1 or 2 and TGF-β2 as anti-metastases in chemoresistant breast cancer. miR-200c has a promising potential as a new treatment for chemoresistant breast cancer, because of its potent pro-apoptotic and anti-metastatic properties.